Wychowanie według Syracydesa - Pudełko, Jolanta Judyta (Verbum vitae, 2012)
The problem of biblical instruction and education is present in various aspects in the Book of Ben Sirach. This book contains a synthesis of tradition of biblical Israel but also shows openness to many positive elements of the Greek culture. Ben Sirach proposes a model of education based on the solid foundation of the Law of God contained in Torah. This model, respected through the attitude of fear of God, leads to true divine wisdom. Man in this process remains free. He can accept or reject Sirach’s request for education. Accepting it he must be aware of the effort connected with the educational process and the goal this process should achieve. The process begins in adolescence although it will last for the rest of man’s life. The best model of education should be the very life of wise men, who by their attitude are the best invitation for prospective students.